Reengineering the Nigerian Civil Service for Optimum Performance: The Path Not Taken: Global Journal of Political Science and Administration. Europe – American. 5(4) August 11, 1-12. - Tom, Edet (Afrischolar Discovery Repository (Annex), 2024)
Civil Service anywhere in the world plays a very significant role in transforming government policies and programmes into reality. In most developing countries in general and Nigeria in particular the performance of Civil Service in discharging its duties is quite below expectation even after many reforms and restructuring had been carried out. The work identified and discussed what needs to be done for optimum performance of the Civil Service in Nigeria. It examined human and environmental factors that hindered Nigeria Civil Service from realization of its intended goals. The work is of the view that the attainment of optimum performance by the Civil Service in Nigeria is predicated upon the level of commitment and fidelity by the leading operator of the service. The work relied on secondary source and observation to gather the data that were used in this work. The work recommended among others that for Nigerian Civil Service to attain optimum performance there must be vigorous and sustained campaign to make propriety the prime mood of the nation’s culture.Visit https://afrischolarrepository.net.ng for more publications.Tom, E. J. (2017). “”.